Comparison of three hydroxyapatite/β‐tricalcium phosphate/collagen ceramic scaffolds: An in vivo study. Issue 4 (4th June 2013) - Maté‐Sánchez de Val, José Eduardo; Mazón, Patricia; Guirado, José Luis Calvo; Ruiz, Rafael Arcesio Delgado; Ramírez Fernández, María Piedad; Negri, Bruno; Abboud, Marcus; De Aza, Piedad N.
Abstract Calcium–phosphate ceramics, which have a composition similar to bone mineral, represent a potentially interesting synthetic bone graft substitute. In the present study, three porous hydroxyapatite (HA)/β‐tricalcium phosphate (β‐TCP)/collagen ceramic scaffolds were developed, characterized, and tested for their bone repairing capacity and osteoinductive potential in a New Zealand Rabbit model. The ratio of the ceramic components HA/‐TCP/collagen varied from 40/30/30 to 50/20/30 and 60/20/20 (in wt %), respectively. None of the ceramic scaffolds succeeded in completely bridging the 6 mm calvarian defect with new bone after 60 days implantation. 60/20/20 ceramic scaffolds showed significantly more bone formation in the pores and in the periphery of the graft than the other two materials. Histomorphometric analysis revealed that the 40/30/30 scaffold produced best bone‐to‐implant contact (67.23 ± 0.34% with higher quality, closer contact) in comparison with 50/20/30 (54.87 ± 0.32%), and 60/20/20 (48.53 ± 0.31%). Both physicochemical and structural properties of the ceramic composites affected their in vivo behavior, either dependently or independently, emphasizing the importance of assessing bone repair parameters individually. The scaffolds may offer clinical applications in reconstructive surgery for treating bone pathologies. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1037–1046, 2014.